Time-integrated and time-resolved photoluminescence studies of InGaN quantum dots - Robinson, J; Rice, J; Jarjour, A; Smith, J; Taylor, R; Oliver, R; Briggs, G; Kappers, M; Humphreys, C; Yasin, S; Arakawa, Y (2004)
We present studies of the optical transitions in InGaN quantum dots (QDs). Spatially-resolved micro-photoluminescence (mu-PL) of single InGaN QDs reveals very sharp, clearly-defined peaks that are characteristic of strongly-confined carriers. Time-resolved measurements for single InGaN QDs reveal single exponential decays in contrast to non-exponential decays from the 2D wetting layer (WL) and from ensemble measurements. (C) 2004 WILEY-VCH Verlag GmbH and Co. KGaA, Weinheim.